'Societal Relationships with Nature': A framework for understanding nature‐related conflicts and multiple values. Issue 2 (21st February 2022) - Berghöfer, Uta; Rode, Julian; Jax, Kurt; Förster, Johannes; Berghöfer, Augustin; Wittmer, Heidi
Abstract: In this paper, we operationalize the concept of Societal Relationships with Nature (SRN) as a framework for understanding nature‐related conflicts and multiple values. Based on three dimensions knowledgescape, interactions and identity, we propose a set of questions for the empirical analysis of conflict situations. We use two case studies—designation of a biosphere reserve in southern Chile and the return of the wolf in Germany—to illustrate how the SRN framework can reveal and structure the complexity of human–nature relationships. From the conceptual advances and the academic debate on multiple values of nature, we derive four requirements for approaches to analyse nature‐related conflicts and how different stakeholders attribute importance to nature. These should (a) cover the relevant aspects and reveal the critical issues underlying a conflict, (b) enable an understanding of differences and commonalities in people's perspectives and positions, (c) be comprehensive enough to uncover important issues in complex situations without losing empirical practicability and (d) take power relations into account. We discuss whether and how the SRN framework meets these requirements. We present the SRN framework in particular to the academic community working at the interface with policy and practice on multiple values of nature and nature‐related conflicts. SRN analysis can also be applied to complement valuation approaches by specifying and explaining differences in people's attributions of value to nature. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Zusammenfassung: Auf Grundlage des Konzepts der Gesellschaftlichen Naturverhältnisse (Societal Relationships with Nature, SRN) entwickelt dieser Artikel einen Analyserahmen zur Untersuchung von naturbezogenen Konflikten und Wertvorstellungen. Die empirische Analyse von Konfliktsituationen erfolgt anhand von Leitfragen für die drei sich ergänzenden Dimensionen Wissenserwerb (knowledgescape), Interaktionen und Identität. Zwei Fallstudien, zur Etablierung eines Biosphärenreservats in Südchile und zur Rückkehr des Wolfs nach Deutschland, illustrieren, wie mit Hilfe des SRN‐Rahmens die Komplexität von Mensch‐Natur‐Verhältnissen offengelegt und strukturiert werden kann. Aus der konzeptionellen Debatte über die multidimensionale Bewertung der Natur leiten wir vier Anforderungen für Analyseansätze zu naturbezogenen Konflikten und divergenten Wertvorstellungen ab. Solche Ansätze sollten (i) alle relevanten und potenziell den Konflikten zugrundeliegenden Aspekte einbeziehen, (ii) die Unterschiede ebenso wie die Gemeinsamkeiten in den Positionen beteiligter Akteursgruppen aufdecken, (iii) trotz der für die Erfassung komplexer Situationen notwendigen Breite der Analyse die praktische Anwendbarkeit gewährleisten, und (iv) Machtgefüge angemessen berücksichtigen. Wir erörtern, inwieweit der SRN‐Rahmen diese Anforderungen erfüllt. Der SRN‐Analyserahmen dürfte insbesondere für Wissenschaftler interessant sein, die an der Schnittstelle zu Politik und Anwendungspraxis zu naturbezogenen Konflikten und Wertvorstellungen arbeiten. SRN Analyse kann beispielsweise Bewertungsansätze ergänzen, um die Gründe für unterschiedliche naturbezogene Wertvorstellungen zu erklären.